2016
DOI: 10.5433/1679-0359.2016v37n4supl1p2807
|View full text |Cite
|
Sign up to set email alerts
|

In situ degradability of elephant grass ensiled with increasing levels of pineapple agro-industrial by-product

Abstract: The objective of this study was to evaluate the in situ degradability of dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF) and hemicellulose of elephant grass (Pennisetum purpureum, Schum.) with increasing levels (0; 35.0; 70.0, 105.0, and 140.0 g kg -1 ) of dried pineapple (Ananas comosus, L.) byproduct (DPBP). The experimental silos consisted of plastic drums with 210 L capacity. After weighing and homogenizing the elephant grass with the DPBP, the material was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
(8 reference statements)
1
8
0
Order By: Relevance
“…The low degradation rates (c) observed for the rumen degradation of ADF with increase in inclusion of DABP (Table 6) may reflect in lower digestibility of the feed and, consequent, a reduction of voluntary intake. The ED did not show significant differences after inclusion of DABP, agreeing with the results obtained in the apparent-digestibility trial for this fraction (FERREIRA et al, 2010). Thus, feed with higher fiber and lignin contents will have lower nutritional value, characterizing it as a low availability to rumen microorganisms, such as DABP, when at high contents of inclusion.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The low degradation rates (c) observed for the rumen degradation of ADF with increase in inclusion of DABP (Table 6) may reflect in lower digestibility of the feed and, consequent, a reduction of voluntary intake. The ED did not show significant differences after inclusion of DABP, agreeing with the results obtained in the apparent-digestibility trial for this fraction (FERREIRA et al, 2010). Thus, feed with higher fiber and lignin contents will have lower nutritional value, characterizing it as a low availability to rumen microorganisms, such as DABP, when at high contents of inclusion.…”
Section: Resultssupporting
confidence: 87%
“…The fraction a, which is composed of carbohydrates and soluble nitrogenous compounds, increased in the treatments with DABP probably due the higher CP content of the by-product (Table 1). Ferreira et al (2016) also observed increase in the soluble fraction when elephant grass was ensiled with five contents of dried pineapple by-product (0; 35; 70; 105 and 140 g kg -1 , as fed), with fraction a values for DM varying from 187.3 to 249.7 and for CP from 178.9 to 233.0 g kg -1 , respectively for silage without and with by-product inclusion of 140 g kg -1 . The rumen microbial flora transforms non-protein nitrogen and degradable protein into microbial protein, when energy is available, and this availability for microorganisms is determined by the rates of degradation and passage through the rumen, which will influence the efficiency and quantity of microbial protein synthesized (SANTOS et al, 2012).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…The contents of the fraction A of NDF were different from the presented for the fraction B of NDF, since the NDF fractions of the silages may present high solubility in water. Effective degradability for the silages at passage rates of 2, 5 and 8% per hour can be considered good when compared to silages from other crops (Ferreira et al 2016). Thus, lower concentrations of effective degradability of NDF is an indicative that the plant should be ensiled younger.…”
Section: Forage Species Production and Degradability Of Silage Chemicmentioning
confidence: 99%